MUC5AC mucin release from human airways in vitro: Effects of indomethacin and Bay X1005. Issue 1 (2001) - Roger, Patricia; Gascard, Jean-Pierre; Bara, Jacques; de Montpreville, Vincent Thomas; Brink, Charles
Abstract : Background : Increased secretion of mucus is a hallmark of many respiratory diseases and contributes significantly to the airflow limitation experienced by many patients. While the current pharmacological approach to reducing mucus and sputum production in patients is limited, clinical studies have suggested that drugs which inhibit the cyclooxygenase and/or 5-lipoxygenase enzymatic pathways may reduce secretory activity in patients with airway disease. Aim : This study was performed to investigate the effects of indomethacin (cyclooxygenase inhibitor) and Bayx1005 (5-lipoxygenase inhibitor) on MUC5AC release from human airways in vitro . Methods : An immunoradiometric assay was used to determine the quantities of MUC5AC present in the biological fluids derived from human airways in vitro . The measurements were made with a mixture of eight monoclonal antibodies (MAbs; PM8) of which the 21 M1 MAb recognized a recombinant M1 mucin partially encoded by the MUC5AC gene. Results : The quantities of MUC5AC detected in the biological fluids derived from human bronchial preparations were not modified after treatment with indomethacin (cyclooxygenase inhibitor) and/or an inhibitor of the 5-lipoxygenase metabolic pathway (BAY x1005). Conclusion : These results suggest that the cyclooxygenase and 5-lipoxygenase metabolic pathways play little or no role in the release of MUC5AC from human airways.